Peranan Teknologi Proses Pengolahan Pangan dalam Penurunan Alergenisitas Kerang-kerangan: Meta-analisis - Andi Nadya Tita Alia; Nurheni Sri Palupi; Puspo Edi Giriwono (Institut Pertanian Bogor, 2023)
Shellfish is widely consumed globally, one of the main reasons is because it contains good nutrition for health. The increased consumption also leads to adverse health problems such as food allergy. Food allergy is hypersensitivity reaction of the immune system caused by consumption or exposure to food. Various food processing methods has been proven to alter shellfish allergenicity with different effectiveness. This study aims to determine the most effective processing method to reduce shellfish allergenicity through meta-analysis. In total of 19 articles were obtained using PRISMA diagram, with publication year range 2006-2020. Data were analyzed to determine Standardized Mean Difference (SMD) with 95% confidence interval. Moist heating, high hydrostatic pressure, irradiation, and ultrasound processing have significant effect (p < 0,05) in reducing shellfish allergenicity. Meanwhile, boiling and roasting processing did not have a significant effect. Based on the results of the meta-analysis, high hydrostatic pressure is the most effective method in reducing shellfish allergenicity because it has the highest effect size value with -7,25 (95% CI: -9,11 s.d. -5,4; p < 0,00001). Keywords: allergenicity, food processing, meta-analysis, shellfish